Groaning tears : ethical and dramatic aspects of suicide in Greek tragedy - Garrison, Elise P. (Mnemosyne, Supplements, 1995)
Groaning Tears examines suicide in Greek tragedy in light of the fifth-century ethical climate. No full-scale work has previously been devoted to this pervasive topic. The particular focus of identifying suicide as a response to the expectations of popular ethics and social demands makes it useful for scholars and students of drama, ethics and sociology. Chapter one establishes the ethical background of audiences in the fifth century while chapters two through five examine suicide in the context of whole plays based on motivational distinctions: to avoid disgrace and preserve an honorable reputation; to avoid further suffering; to end grief; and to sacrifice oneself for a greater good. The final chapter considers a drama of lighter tone that presents suicide in all of its ethical and theatrical aspects.